Financial literacy training and introduction to SI APIK for the Darul Hijrah Madani bazaar group, Kolhua, Kupang - Hironnymus Jati; Indri Astuti (Universitas Muhammadiyah Magelang, 2022)
Financial literacy has become a concern for all stakeholders and is now acknowledged as one of the pillars to the success and long-term viability of the micro and small-scale food industry. Accounting literacy is critical for MSMEs because they are the economy's key drivers and the largest source of jobs in Indonesia. Members of the Darul Hijrah Bazaar face challenges such as a lack of financial literacy, difficulty documenting financial transactions, and compiling and presenting financial reports. This program seeks to improve financial literacy by using the SI APIK application to record transactions and financial reports. Lectures on saving, investing, money management, and risk, as well as an introduction to the Android-based SI APIK accounting program, a tutorial on grouping business transactions by business sector, a demonstration of recording financial transactions, and assistance are among the methods employed. Through SI APIK for Android, this program can increase partners' financial and accounting literacy, allowing them to create financial reports for their businesses. This program can be expanded so that all bazaar members can run their businesses on a regular and sustainable basis.